Structural Studies of a Bacterial tRNA(HIS) Guanylyltransferase (Thg1)-Like Protein, with Nucleotide in the Activation and Nucleotidyl Transfer Sites - Hyde, Samantha J. (Public Library of Science, 2013)
All nucleotide polymerases and transferases catalyze nucleotide addition in a 5′ to 3′ direction. In contrast, tRNA(His) guanylyltransferase (Thg1) enzymes catalyze the unusual reverse addition (3′ to 5′) of nucleotides to polynucleotide substrates. In eukaryotes, Thg1 enzymes use the 3′–5′ addition activity to add G(−1) to the 5′-end of tRNA(His), a modification required for efficient aminoacylation of the tRNA by the histidyl-tRNA synthetase. Thg1-like proteins (TLPs) are found in Archaea, Bacteria, and mitochondria and are biochemically distinct from their eukaryotic Thg1 counterparts TLPs catalyze 5′-end repair of truncated tRNAs and act on a broad range of tRNA substrates instead of exhibiting strict specificity for tRNA(His). Taken together, these data suggest that TLPs function in distinct biological pathways from the tRNA(His) maturation pathway, perhaps in tRNA quality control. Here we present the first crystal structure of a TLP, from the gram-positive soil bacterium Bacillus thuringiensis (BtTLP). The enzyme is a tetramer like human THG1, with which it shares substantial structural similarity. Catalysis of the 3′–5′ reaction with 5′-monophosphorylated tRNA necessitates first an activation step, generating a 5′-adenylylated intermediate prior to a second nucleotidyl transfer step, in which a nucleotide is transferred to the tRNA 5′-end. Consistent with earlier characterization of human THG1, we observed distinct binding sites for the nucleotides involved in these two steps of activation and nucleotidyl transfer. A BtTLP complex with GTP reveals new interactions with the GTP nucleotide in the activation site that were not evident from the previously solved structure. Moreover, the BtTLP-ATP structure allows direct observation of ATP in the activation site for the first time. The BtTLP structural data, combined with kinetic analysis of selected variants, provide new insight into the role of key residues in the activation step.